Impacto del proyecto de inversión de incentivos forestales del Ministerio de Agricultura, Ganadería, Acuacultura y Pesca, en la Provincia de Los Ríos, período 2013 - 2015 - Ibarra Álava, Ruth Virginia (2016)
Impact assessment of the Investment Program of Forestry Incentives (PIIF), where the following specific objectives were set: Check the number of beneficiaries, hectares and species planted in the province Los Rios, period 2013-2015; analyze the survival of forest plantations in the period 2014 - 2015, in order to determine the percentage of payment of Forestry Incentive and determine the perception of the impact on beneficiaries of Project Investment Forestry Incentives to achieve the results we used the 2015, on the number of proposals species hectares, cantons, beneficiaries and analysis - following research methodology type of nonparametric statistics for the first goal, and second values of the database MAGAP the period 2013 took survival to determine whether the PIIF has met the goal of reforestation; and the third objective perception of 100 panelist expressed through a proposed 12-item Likert with 5 options and questionnaire responses was assessed. These results were plotted in graphs and tables showing results for the period 2013 - 2015 sponsored by the PIIF and perception beneficiaries an analysis of each item showing the impact that has had the program for each target beneficiaries PIIF are 33 for people legal and 69 for individuals, with a total of 6933.70 has reforested and more species are planted with melina 2824.10, 2142.01 teak, balsa 1641.31, rubber and eucalyptus 164.28 162 hectares, with the following melina percentage with 41%, 31% teak, balsa 24%, rubber and eucalyptus 2%. The raft is the only native species PIIF. En 2013 O. pyramidale plantations has better survival of 87.15 while 84.81 T. grandis and G. arborea 2014 98.63, H. brasilienses 97.5, T. grandis with 94.14 and 85.05 O. pyramidale; Items 1 to 7, according to the perception of the panelists was yes so applied methodology Likert there is no significant statistical difference, while 8 to 12 if no statistical difference, this is because the panelists were any questions or disagreed with these aspects.